2020
DOI: 10.3390/cells9112365
|View full text |Cite
|
Sign up to set email alerts
|

Neurofibromin Structure, Functions and Regulation

Abstract: Neurofibromin is a large and multifunctional protein encoded by the tumor suppressor gene NF1, mutations of which cause the tumor predisposition syndrome neurofibromatosis type 1 (NF1). Over the last three decades, studies of neurofibromin structure, interacting partners, and functions have shown that it is involved in several cell signaling pathways, including the Ras/MAPK, Akt/mTOR, ROCK/LIMK/cofilin, and cAMP/PKA pathways, and regulates many fundamental cellular processes, such as proliferation and migratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
73
0
8

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(95 citation statements)
references
References 163 publications
0
73
0
8
Order By: Relevance
“…Neurofibromin is a large protein that presents a GTPase-activating protein (GAP) related domain (GRD) [ 11 ]. Therefore, as other GAP proteins, one of its functions is to accelerate the hydrolysis of Ras-GTP to Ras-GDP, converting the active GTP (guanosine triphosphate) bound form to an inactive GDP (guanosine diphosphate) bound form, and thereby negatively regulating the Ras signal [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neurofibromin is a large protein that presents a GTPase-activating protein (GAP) related domain (GRD) [ 11 ]. Therefore, as other GAP proteins, one of its functions is to accelerate the hydrolysis of Ras-GTP to Ras-GDP, converting the active GTP (guanosine triphosphate) bound form to an inactive GDP (guanosine diphosphate) bound form, and thereby negatively regulating the Ras signal [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Neurofibromin is located in the cytoplasm, but can also be found in the nucleus and associated with plasma membrane microdomains [ 9 , 10 ]. Therefore, neurofibromin is considered a multifunctional protein that affects several cellular processes in cells of different tissues [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Neurofibromatosis type 1 (NF1, MIM #162200), also known as Von Recklinghausen disease, is a very complex though relatively common genetic condition characterized by a heterogeneous involvement of several organ systems [ 1 , 2 ]. This multifaceted disorder is caused by autosomal dominantly inherited or de novo pathogenic variants in NF1 (MIM *613113), a large tumor suppressor gene located at 17q11.2 and spanning ~350 kb of genomic DNA sequence [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…NF1 is caused by heterozygous inactivating mutations of the NF1 gene, with approximately half of the cases being sporadic. This gene spans about 350 kb on 17q11.2 [ 3 , 4 ] and encodes neurofibromin, which inhibits the RAS pathway through GRD, a specific GTPase activation domain [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the NF1 gene displays a complex splicing pattern in order to generate a great diversity of transcripts: 5 inframe exons undergo alternative splicing (exon 9a, exon 10a-2, exon 23a, exon 43, and exon 48a) [ 4 ]. Alternative splicing also includes the skipping of some exons (such 29 or 30 or both) or the N-isoform with additional 241 base pairs (bp) of intron 10c and several additional shorter transcripts whose physiological significance remains unclear [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%